Five ways to get a grip on the need to include clinical placements in Indigenous settings - Ansell, Alexandra (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Educational organizations that train medical professionals are intricately linked to the responsibility of creating culturally safe healthcare providers. However, prevailing inequities contribute to the continued oppression of Indigenous peoples, evidenced by inequitable access, treatment, and outcomes in the healthcare system. Despite an increasing awareness of how colonialist systems and the structures within them can contribute to health disparities, this awareness has not led to drastic improvements of health outcomes for Indigenous peoples. Many recently graduated health professionals will have likely encountered Indigenous peoples as a minority population within the larger, non-Indigenous context. Clinical placements in Indigenous settings may improve recruitment and retention of healthcare professionals in rural and remote settings, while helping educational institutions fulfill their social accountability missions. These placements may aid in the decolonization of care through reductions in bias and racism of medical professionals. Clinical placements in Indigenous settings may better prepare providers to navigate the dynamic challenges of the healthcare needs of Indigenous peoples safely and respectfully.